2008
DOI: 10.1007/s10038-008-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlations analysis of mutations in the phenylalanine hydroxylase (PAH) gene

Abstract: The aims of our research were to define the genotype-phenotype correlations of mutations in the phenylalanine hydroxylase (PAH) gene that cause phenylketonuria (PKU) among the Israeli population. The mutation spectrum of the PAH gene in PKU patients in Israel is described, along with a discussion on genotypephenotype correlations. By using polymerase chain reaction/denaturing high-performance liquid chromatography (PCR/dHPLC) and DNA sequencing, we screened all exons of the PAH gene in 180 unrelated patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
1
28
0
4
Order By: Relevance
“…Since the genotype determines the activity of PAH and thus the metabolic phenotype, there is growing evidence of genotype–phenotype correlation [Trefz et al., ; Kayaalp et al., ; Benit et al., ; Jennings et al., ; Kasnauskiene et al., ; Pey et al., ; Bercovich et al., ; Daniele et al., ; Bueno et al., Polak et al., ; Reblova et al., ; Tao et al., ; Trunzo et al., ]. It has been known for about 20 years that PAH activity predicts the clinical phenotype (blood Phe) in PKU [Eisensmith and Woo, ].…”
Section: Now: a Closer Look At The Molecular Genetics Of Pkumentioning
confidence: 99%
“…Since the genotype determines the activity of PAH and thus the metabolic phenotype, there is growing evidence of genotype–phenotype correlation [Trefz et al., ; Kayaalp et al., ; Benit et al., ; Jennings et al., ; Kasnauskiene et al., ; Pey et al., ; Bercovich et al., ; Daniele et al., ; Bueno et al., Polak et al., ; Reblova et al., ; Tao et al., ; Trunzo et al., ]. It has been known for about 20 years that PAH activity predicts the clinical phenotype (blood Phe) in PKU [Eisensmith and Woo, ].…”
Section: Now: a Closer Look At The Molecular Genetics Of Pkumentioning
confidence: 99%
“…However, the pathogenic mutations in New South Wales have not been previously studied. Phenotype-genotype correlations in PKU have shown clear associations between some mutations and the severity of disease (Kayaalp et al 1997;Bénit et al 1999;G€ uttler et al 1999;Zschocke 2003;Bercovich et al 2008). Due to the large number of mutations and the low population frequency of some of these mutations, it is often difficult to ascertain the phenotypic consequences of a given mutation and correlations may also give rise to conflicting results (Bercovich et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between two different mutant polypeptides in the tetrameric enzyme molecule increase disease complexity. The large number of possible allelic combinations makes prediction of the phenotype difficult (Dipple and McCabe, 2000;Scriver and Kaufman, 2001;Kasnauskiene et al, 2003;Kim et al, 2006;Bercovich et al, 2008;Danielle et al, 2009). In vitro expression analysis studies have demonstrated a large range of residual activities among different mutations (null to 75%) (Waters et al, 1998;Jennings et al, 2000;Waters, 2003).…”
Section: Introductionmentioning
confidence: 99%